Penguatan Pendidikan Karakter Peserta Didik SD Negeri 2 Ngabeyan Melalui Cerita Sejarah Kemerdekaan Indonesia - Wulandari, Hesti (Universitas Sebelas Maret, 2022)
This research was motivated by the Strengthening Character Education program by the Ministry of Education and Culture in each educational unit. This research aims to describe the strengthening of character education for students at Public Elementary School 2 Ngabeyan and to find out to what extent and how Strengthening Character Education is implemented through stories about the history of Indonesian independence. This research is a qualitative research approach combined with descriptive methods. The subjects of this research were 25 students at Public Elementary School 2 Ngabeyan in grades III and IV. Data analysis techniques include data reduction, data presentation, and withdrawal. conclusion. The procedure used is to describe and analyze data in the field. The approach in this research uses a pedagogical, psychological and ethnomusicological approach. Techniques for collecting data are by means of participant observation, structured interviews and documentation studies. The data validity technique uses data triangulation. Data analysis techniques using data collection, data reduction, data presentation and data verification. The results of the research show that the story of the history of Indonesian independence functions as a medium for strengthening students' character education through instilling personality values by forming behavioral habits in accordance with the instillation of strengthening character education including religious, nationalist, independence, mutual cooperation and integrity values.